Investigation of electron-beam deposition and related damage in p-Si by means of Laplace and conventional deep-level transient spectroscopy - Meyer, W.E. (Walter Ernst) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.